(untitled) (Nordic Journal of Practical Theology, 2026)
The article starts by tracing the establishment of the diacon as a professional practice in the Church of Norway in the 20thcentury. However, in contrast to Sirris, the article argues that this establishment does not entail a “shift in paradigm” when it comes to the knowledge foundation of the profession. Rather, the articles argues that the ethos of care of the health-care professions represent a continuity across the 20th century. Turing to the British theorist of cybernetics James Bridle, the article explores how other kinds of knowledge foundations for the professional practice of diacons would allow other social challenges to be discursively produced as diaconal challenges. Imagining different kinds of knowledge foundations for diaconal would equip diacons to address such challenges beyond the care ethos of the health care professionals.